Functional Evaluation of Fracture Shaft of Humerus Treated By Antegrade Closed Interlocking Nail - Gupta, Pradip Kumar; Chaudhary, Ajay (Birat Journal of Health Sciences, 2020)
Introduction: Management of fractures shaft of humerus is always a challenging problem to deal with as they are very frequently associated with complex multiple injuries. Interlocking nails have gained popularity now a days for stabilization of humeral shaft fractures due to load sharing nature of implant, preservation of fracture hematoma, minimal exposures and rigid fixation with early mobilization. Objective: The objective of the study was to assess the outcome of the fracture shaft of humerus stabilized with interlocking nail. Methodology: A Prospective clinical study was done on fifty patients of fractures shaft of humerus stabilized using antegrade interlocking nail. Results: The most common causes of fractures shaft of humerus was road traffic accident (66%). The average union time was 12.7± 1.3 weeks. About 8% had delayed union and 10% had non-union which were treated with bone graft. There was no deep infection but two (4%)had superficial infection in open Gustilo grade II fracture. Four cases (8%) had radial nerve injury, mostly neuropraxias, which recovered in three months. There were 12 cases of significant restriction of shoulder movements which was resolved in six weeks after guarded physiotherapy. Conclusion: Closed interlocking nailing is a least invasive surgical option available to manage complex humeral shaft fractures.